Analisis Tingkat Kepuasan Pembeli Ditinjau Dari Fasilitas Lokasi Perbelanjaan (Studi Kasus Di Pasar Pusat Pasar Medan) - Allan Simonsen Saragih; Rismayani; Sri Mulyani (Information Technology and Science (ITScience), 2019)
The decreasing number of consumers are becoming a major factor sluggishness traditional market competitiveness . Some of the main reasons customers make the shift from traditional markets to modern markets among others , the existence of the decline of traditional markets is not entirely due to the modern market . Due to the fact that the declining traditional market turnover is also influenced by the availability of facilities given to the buyer . The facility consists of a non- physical facilities and physical facilities . The purpose of this study was to determine the influence of physical facilities and non-physical facilities to customer satisfaction in Pasar Pusat Pasar , and analyze the most dominant factor influencing customer satisfaction of shopping at Pasar Pusat Pasar Medan. By using multiple regression analysis , the result showed that non- physical facilities and physical facilities of 45.8 % impact on customer satisfaction shopping at Pasar Pusat Pasar , while 54.2 % influenced by other factors not examined in this study . Factors of physical facilities provide the most dominant influence on customer satisfaction Market shopping at Pasar Pusat Pasar . Security during and after shopping , the air around the hot market , odorless , neat arrangement of goods as well as the friendliness of the seller into the factors affecting shopping convenience.